Facile processing of Si-Cu core-shell as potential meta-atom materials - Salim M.A.; Misran H.; Othman S.Z.; Shah N.N.H.; Razak N.A.A.; Abdullah H. (2023)
Monodispersed spheres of Si-Cu core-shell nanocomposite with silica as core and copper as shell were successfully synthesized by a modified two-step synthesis method. Spherical particles of silica core were first synthesized using a modified Stber method using nonsurfactant template. The obtained monodispersed silica spheres were successfully coated with copper through a modified sol-gel method employing nonsurfactant template. A renewable nonsurfactant template (decyl alcohol) was successfully used to modify the silica surfaces. To study the effect of nonsurfactant template on copper deposition onto silica surfaces, various compositions of nonsurfactant template were used. The X-ray diffraction patterns of core-shell nanocomposite exhibited monoclinic copper crystalline phase and a broad peak characteristic of amorphous silica networks. The results from field emission scanning electron microscopy (FE-SEM) suggested that both monodispersed silica core as well as Si-Cu core-shell particle sizes were at ca. 560 nm. UV-Vis spectrum of Si-Cu core-shell exhibited a broad absorption peak centered at ca. 394 nm suggesting optical properties of these Si-Cu nanocomposite as potential meta-atom materials. 2012 IEEE.